2023
DOI: 10.21037/gs-23-51
|View full text |Cite
|
Sign up to set email alerts
|

Determining whether the diagnostic value of B-ultrasound combined with contrast-enhanced ultrasound and shear wave elastography in breast mass-like and non-mass-like lesions differs: a diagnostic test

Abstract: Background: Mass-like (ML) and non-mass-like (NML) are two manifestations of breast lesions on ultrasound. Contrast-enhanced ultrasound (CEUS) can make up for the limitation of B-ultrasound (US) in the observation of focal blood flow, and shear wave elastography (SWE) can supplement the hardness information of the lesion. The present study aimed to analyze the characteristic manifestations of US, CEUS, and SWE in NML and ML breast and evaluate whether the diagnostic performance of these three ultrasound techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…[ 26 ] Li S-Y et al analyzed the features of breast non-mass lesions on B-mode US, CEUS, and shear-wave elastography (SWE) and discovered that the combination of conventional US and SWE had the highest AUC of 0.935. [ 14 ] Wang F et al explored the combined application of SWE and a novel blood flow imaging technique called Angio PLUS microvascular US imaging for diagnosing breast non-mass lesions and found an accuracy of 78.3% to 88.3%. [ 27 ] These studies indicated that sonoelastography played a good complementary role on conventional US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] Li S-Y et al analyzed the features of breast non-mass lesions on B-mode US, CEUS, and shear-wave elastography (SWE) and discovered that the combination of conventional US and SWE had the highest AUC of 0.935. [ 14 ] Wang F et al explored the combined application of SWE and a novel blood flow imaging technique called Angio PLUS microvascular US imaging for diagnosing breast non-mass lesions and found an accuracy of 78.3% to 88.3%. [ 27 ] These studies indicated that sonoelastography played a good complementary role on conventional US.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that sonoelastography has important value in the diagnosis of breast diseases, especially for non-mass lesions. [ 13 , 14 ] The aim of our study was to summarize the diagnostic performance of sonoelastography for breast non-mass lesions and determine the application value of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, clinical nomograms have been applied to breast diseases in numerous aspects, such as predicting breast cancer, assessing the diagnostic performance of imaging methods in breast diseases ( 18 – 21 ), predicting axillary lymph node metastasis of breast cancer ( 22 ), and predicting the recurrence rate and risk of breast cancer ( 23 ), etc. In the ultrasonic differentiation between SA and malignant tumors, the findings of Liang’s study were consistent with ours ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with IDC, the size of SA nodules is smaller, and SA does not clinically manifest symptoms, thereby complicating palpation and preoperative ultrasonic diagnosis. Therefore, this ultrasound-based comparative study between SA and IDC enabled the construction of a nomogram to assist ultrasound physicians in not only further analyzing the value of various ultrasonic features in SA diagnosis but also calculating the total score on the nomogram to predict the risk of SA (17)(18)(19). Our research indicated that age, nodule size, menopausal status, presence of clinical symptoms, palpability of lesions, margins, internal echo, CDFI grading, and RI could be used as predictive factors for distinguishing between SA and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is frequently used in detecting and screening breast cancer since it is a secure, non-invasive, and affordable imaging technique. Breast lesions, both benign and malignant breast lesions, can be more accurately diagnosed using multimodal ultrasonography [12][13][14][15][16] . TNBC frequently exhibits the characteristics of benign tumors on conventional ultrasound imaging, even though various molecular subtypes of breast cancer might exhibit diverse appearances on sonogram s [17] .…”
Section: Introductionmentioning
confidence: 99%